Reflections on the scope of districts’ Reading and Writing Plan, IED Villas del Progreso - Páez Vigoya, Doris Adriana (Rastros Rostros, 2020)
The purpose of this article is to publicize the scope of the implementation of Plan Distrital de Lectura y Escritura (PDLE) in Bogotá, specifically the educational intervention process carried out at the Villas del Progreso IED, located in Bosa. The PDLE emerged in 2016 from the SED as an alternative to improve the reading and writing processes of children, and proposed intervention actions for third grade students in institutions with low performance on the 2012, 2014 and 2016 in Pruebas Saber. From the development of the intervention plan and pedagogical accompaniment, it was proposed to carry out a diagnostic phase with the students to recognize the difficulties in communicative abilities, later, to review the proposed objectives throughout the implementation to know the impact of the PDLE in situ. Based on this experience, the curriculum of the language subject was restructured, which helped to improve the pedagogical designs of teachers and strengthened professional training by addressing the needs of the socio-cultural context of the institution. Consequently, this article seeks to present the types of participation that took place in the framework of the intervention and the project. Similarly, it aims to assess the scope of both teacher training processes and classroom experiences